Apakah Jenjang Pendidikan Dasar Tenaga Kerja Berperan dalam Mengurangi Kemiskinan di Indonesia? - Rizal, Rofiq Nur (Jurnal Ekonomi dan Pembangunan Indonesia, 2015)
Improving the quality of human resources through education is believed as one of the solutions to reduce poverty. World attention to education in global ’Education For All program’ and the ’Millennium Development Goals’, suggests that basic education become central program in reducing poverty. If there was a linear relationship between education and income, improved education at basic level would not increase revenues substantially. This study aim is analyzing the role of labor education level toward poverty. Using panel data, this study found that basic education level of labor has a significant role to increase poverty, whereas higher education levels of labor significantly reduce poverty in Indonesia.